2018
DOI: 10.1126/scisignal.aat7951
|View full text |Cite
|
Sign up to set email alerts
|

Covalent inhibitors of EGFR family protein kinases induce degradation of human Tribbles 2 (TRIB2) pseudokinase in cancer cells

Abstract: A major challenge associated with biochemical and cellular analysis of pseudokinases is a lack of target-validated small-molecule compounds with which to probe function. Tribbles 2 (TRIB2) is a cancer-associated pseudokinase with a diverse interactome, including the canonical AKT signaling module. There is substantial evidence that human TRIB2 promotes survival and drug resistance in solid tumors and blood cancers and therefore is of interest as a therapeutic target. The unusual TRIB2 pseudokinase domain conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 108 publications
3
83
0
Order By: Relevance
“…Abnormally elevated TRIB2 was previously identified as the clinically relevant factor in various subtypes of human cancers . As described previously, TRIB2 promotes tumorigenesis and induces therapeutic resistance by activating Wnt‐mediated downstream activation of Hippo signaling and the YAP pathway through transcriptional control of gene expression and TRIB2‐mediated posttranslational regulation of protein stability in liver cancer cells .…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Abnormally elevated TRIB2 was previously identified as the clinically relevant factor in various subtypes of human cancers . As described previously, TRIB2 promotes tumorigenesis and induces therapeutic resistance by activating Wnt‐mediated downstream activation of Hippo signaling and the YAP pathway through transcriptional control of gene expression and TRIB2‐mediated posttranslational regulation of protein stability in liver cancer cells .…”
Section: Discussionmentioning
confidence: 66%
“…Abnormally elevated TRIB2 was previously identified as the clinically relevant factor in various subtypes of human cancers. [5][6][7][8] As MAP3K1 is a 196-kDa serine/threonine kinase that is activated by various stimuli and cell stresses, including growth factors, cytokines, and microtubule disruption. 35 Our present study showed elevated MAP3K1 expression in glioma, which is conversely associated with a poor prognosis and therapeutic resistance in glioma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That some of the active compound-cysteine interactions led to protein degradation without requiring a separate E3 ligase-directing ligand (e.g., EV-3-mediated degradation of BIRC2/3) underscores the potential for covalent modification by small molecules to directly affect protein stability in cells (Foulkes et al, 2018;Jones, 2018;Schreiber, 2019;Yang et al, 2019). We do not yet understand how EV-3 promotes BIRC2 and BIRC3 degradation, but this could involve disruption of protein-protein interactions proximal to the compound-modified cysteines in these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to WT Aurora A, incorporation of the C290A mutation had no effect on protein thermostability (T m ~40 °C, fig. S4B) measured by DSF , Foulkes et al, 2018 or ∆T m values induced by ATP or MLN8237 binding ( fig. S4C).…”
Section: Identification Of Cys 290 As the Site Of Aurora A Redox Regumentioning
confidence: 99%